Cps1 Compliance-Constrained Agc Gain Determination for a Single-Balancing Authority - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2014)
The integration of non-dispatchable generation has increased the need for ancillary services to maintain frequency control performance, and the determination of adequacy to ensure reliability has become an important operating concern. This work determines the AGC gain of a single balancing authority interconnection in order for system frequency to comply with NERC control performance standards, ensuring secondary control adequacy. The particular case of wind expansion is considered, and a simulation of ERCOT is presented to evaluate the performance of the formulation. © 2013 IEEE.
Keywords: Power system dynamics; power system simulation; secondary frequency control; wind power generation